The lived Experience of eudaimonic well-being in a religio-economical role: a phenomenological study / Jalilah Ahmad … [et al.] - Ahmad, Jalilah; Mohd. Roslin, Rosmimah; Abdul Kadir, Mohd. Ali Bahari; Ahmad Nathari, Nur Syafiqah (Penerbit UiTM (UiTM Press), 2019)
This phenomenological study aimed to identify and describe the general meaning structure of eudaimonic well-being experience in performing the role of halal executive. We interviewed three halal executives about their lived experiences with eudaimonic well-being and analysed the data with Giorgi’s descriptive phenomenological method. The general meaning structure describes eudaimonic well-being in performing the role of Halal executive as a phenomenon that interweaves three constituents: (1) awareness of an urgency for change, (2) striving for excellence in a malleable mind-set and (3) confrontation and intense involvement with inner potencies. We discuss these findings in relation to relevant literature on change, eudaimonic well-being, and inner potencies.